Exploring the effects of silver, silica-coated silver, and gold nanoparticles on lipid vesicles: Insights from LUVs and GUVs - Martin, Cibely S. [UNESP]; Maximino, Mateus D. [UNESP]; Martins, João F.V.A. [UNESP]; Pazin, Wallance M. [UNESP]; Constantino, Carlos J.L. [UNESP] (Elsevier, 2024)
Understanding the interaction between nanoparticles (NP) and lipid membranes is crucial for various biomedical applications. In this study, we investigated the effects of silver nanoparticles (AgNP), silica-coated silver nanoparticles (Ag@SiO2), and gold nanoparticles (AuNP) on 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) lipid vesicles. The dynamic light scattering (DLS) and zeta potential measurements were employed to evaluate DOPC large unilamellar vesicles (LUVs) exposed to AgNP, AgNP@SiO2, or AuNP for 180 min. The DOPC giant unilamellar vesicles (GUVs) exposed to the same NP were evaluated by phase-contrast microscopy. The AgNP showed higher reactivity along the exposition time, leading the vesicles to rupture (LUVs and GUVs). The SiO2 coating from Ag@SiO2 decreases the rupture effects compared to uncovered AgNP, showing surface adsorption and, consequently, vesicle morphological changes. The AuNP showed a partial wrapping on the GUVs bilayer and permeation on the LUVs, however the integrity of the bilayer structure is maintained in both GUVs and LUVs. These findings highlight the varying effects of AgNP, Ag@SiO2, and AuNP on lipid vesicles, underscoring the importance of nanoparticle material and coating in their interactions with biological membranes.
Keywords: DOPC; Mimetic system; Nanoparticles; Vesicles